2014
DOI: 10.1002/jor.22772
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical impairments and movement patterns during gait in patients with end‐stage hip osteoarthritis

Abstract: Patients with hip osteoarthritis demonstrate limited range of motion, muscle weakness and altered biomechanics; however, few studies have evaluated the relationships between physical impairments and movement asymmetries. The purpose of this study was to identify the physical impairments related to movement abnormalities in patients awaiting total hip arthroplasty. We hypothesized that muscle weakness and pain would be related to greater movement asymmetries. Fifty-six subjects who were awaiting total hip arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 17 publications
4
59
1
Order By: Relevance
“…Nine pairs of joint couplings were chosen for the analysis in this study and include: hip flexion-extension/knee flexion-extension, hip flexion-extension/knee abduction-adduction, hip flexion-extension/knee rotation, hip abduction-adduction/knee flexion-extension, hip abduction-adduction/knee abduction-adduction, hip abduction-adduction/knee rotation, hip rotation/knee flexion-extension, hip rotation/knee abduction-adduction and hip rotation/knee rotation. These couplings were chosen as many studies have demonstrated hip and knee sagittal plane differences as an effect of hip OA (Eitzen et al, 2012; Hurwitz et al, 1998; Hurwitz et al, 1997; Kiss, 2010; Watelain et al, 2001; Zeni et al, 2014) yet only a few of these studies analyzed frontal and transverse plane rotations of the hip (Watelain et al, 2001; Zeni et al, 2014). γij=tan1true(yi+1,jyi,jxi+1,jxi,jtrue)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine pairs of joint couplings were chosen for the analysis in this study and include: hip flexion-extension/knee flexion-extension, hip flexion-extension/knee abduction-adduction, hip flexion-extension/knee rotation, hip abduction-adduction/knee flexion-extension, hip abduction-adduction/knee abduction-adduction, hip abduction-adduction/knee rotation, hip rotation/knee flexion-extension, hip rotation/knee abduction-adduction and hip rotation/knee rotation. These couplings were chosen as many studies have demonstrated hip and knee sagittal plane differences as an effect of hip OA (Eitzen et al, 2012; Hurwitz et al, 1998; Hurwitz et al, 1997; Kiss, 2010; Watelain et al, 2001; Zeni et al, 2014) yet only a few of these studies analyzed frontal and transverse plane rotations of the hip (Watelain et al, 2001; Zeni et al, 2014). γij=tan1true(yi+1,jyi,jxi+1,jxi,jtrue)…”
Section: Methodsmentioning
confidence: 99%
“…are widely used in understanding the effects of hip joint OA on gait patterns (Eitzen et al, 2012; Foucher et al, 2012; Hurwitz et al, 1998; Hurwitz et al, 1997; Watelain et al, 2001). Specifically, hip joint sagittal plane range of motion was reduced in those with hip OA when compared to healthy controls (Eitzen et al, 2012; Hurwitz et al, 1998; Hurwitz et al, 1997; Kumar et al, 2015; Zeni et al, 2014). Those with hip OA also demonstrated reduced hip extension in late stance (Eitzen et al, 2012; Watelain et al, 2001; Zeni et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies evaluating walking in hip OA suggest a compensatory ipsilateral trunk lean can develop with disease progression (Thurston, 1985;Watelain et al, 2001;Zeni et al, 2015), representing a strategy to reduce the HADM, demand on the hip abductor muscles and provocative joint contact forces. The present data imply individuals with GT (and no evidence of intra-articular pathology) do not alleviate load on the weak and painful lateral hip structures using this compensatory strategy.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In gait analysis studies on selected outcomes, hip OA patients demonstrate abnormal gait patterns characterized by altered joint kinematics [9] and increased lateral trunk lean toward the affected limb before [10] and even years after surgical treatment [11;12]. Furthermore, patients continue to walk at 26% slower selfselected speeds and reduced sagittal hip range of motion relative to age-matched healthy individuals [13;14], and hip muscle weakness in the affected leg, persists for years [15;16].…”
Section: Introductionmentioning
confidence: 99%